Forgiveness as a multidimensional emotion regulation process and its association with childhood emotional wounds in early adulthood - Khairunnisa Salsabila; Sukmarani Sukmarani; Jatu Anggraeni (Empathy : Jurnal Fakultas Psikologi, 2026)
This study aims to examine the relationship between the dimensions of forgiveness (avoidance motivation, revenge motivation, and benevolence motivation) and childhood emotional wounds in early adulthood from the perspective of motivational theories of forgiveness. Although previous research has demonstrated that forgiveness is associated with psychological well-being, the multidimensional mechanisms linking each dimension of forgiveness to childhood emotional wounds remain insufficiently understood. This study employed a quantitative correlational design involving 234 early-adulthood university students (M = 20.87; SD = 1.42; 78.6% female). Data were collected using validated Likert-scale psychological instruments and analyzed using Pearson product–moment correlation. The results indicated that avoidance motivation (r = -0.232; p < 0.001) and revenge motivation (r = -0.304; p < 0.001) were significantly negatively associated with childhood emotional wounds, whereas benevolence motivation showed no significant relationship (r = -0.028; p = 0.670). These findings suggest that reductions in childhood emotional wounds are more closely associated with decreases in negative motivations rather than increases in benevolent intentions toward others. Theoretically, the results reinforce the view that forgiveness is a multidimensional emotion regulation process rather than merely a prosocial orientation. Practically, emotion regulation-based interventions such as mindfulness and cognitive restructuring may be utilized to reduce avoidance and revenge motivations among individuals with past emotional wounds.